2016
DOI: 10.1111/ele.12596
|View full text |Cite
|
Sign up to set email alerts
|

The population ecology of male gametophytes: the link between pollination and seed production

Abstract: The fate of male gametophytes after pollen reaches stigmas links pollination to ovule fertilisation, governing subsequent siring success and seed production. Although male gametophyte performance primarily involves cellular processes, an ecological analogy may expose insights into the nature and implications of male gametophyte success. We elaborate this analogy theoretically and present empirical examples that illustrate associated insights. Specifically, we consider pollen loads on stigmas as localised popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 78 publications
(192 reference statements)
1
32
0
3
Order By: Relevance
“…, Aizen and Harder , Burd , Harder et al. ). Thanks to this vast amount of work, the ecological and evolutionary consequences of variable pollinator service at different scales are now reasonably well understood.…”
Section: Introductionmentioning
confidence: 99%
“…, Aizen and Harder , Burd , Harder et al. ). Thanks to this vast amount of work, the ecological and evolutionary consequences of variable pollinator service at different scales are now reasonably well understood.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in the present study, we tested pollen competition within a single paternal individual from a single pollination event, whereas pollination by multiple pollen donors, with variation in the timing of pollen deposition, may be more likely in nature. In this case, poor‐quality pollen grains could exclude late arriving high‐quality pollen grains from ovule fertilization, thus diminishing the rate of increase in seed set with increasing pollen numbers in natural populations, compared with our experimental population (Harder, Aizen, & Richards, ). Finally, we constrained blossom seed set to a maximum of three seeds, possibly increasing the chances of these seeds to mature compared to the possible nine seeds produced in natural populations.…”
Section: Discussionmentioning
confidence: 83%
“…Although three pollen grains per stigma should be sufficient to achieve a full seed set (three seeds) in D. scandens, we observed that 19 pollen grains were required on average. This might be due to a minimum pollen load necessary to initiate pollen-tube germination (Brewbaker & Kwack, 1963), and positive density-dependent effects facilitating pollen germination at moderate densities (Harder et al, 2016). Furthermore, pollen mortality due to physiological causes or poor genetic quality may eliminate pollen grains before the onset of pollen-tube competition (Harder et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…We assumed that ovule fertilization required germination of at least five pollen grains, whereas the probability that a particular pollen tube reaches the ovary generally declines with increasing stigmatic pollen receipt owing to pollen‐tube competition (Harder et al. , b). Such density‐dependent pollen‐tube success has two consequences.…”
Section: Discussionmentioning
confidence: 99%